Fortidsløse fantaster: Finans og presse hos Trollope og Zola - Gammelgaard, Signe Leth; Nielsen, Jakob Gaardbo (K&K - Kultur og Klasse, 2019)
The latter half of the 19th century saw a rise in novels focusing directly on the stock-exchange and its various actors. Scholarship on these has naturally zoomed in on the main character of the speculator and on the economic paradigm of speculation and financialization, and to a lesser degree concerned itself with the information circuits of the field. However, these studies almost invariably stay rooted within the national literatures; in this article we address the issue of comparativism within the stock-exchange novel, zeroing in on two rather canonical works, namely Anthony Trollope’s The Way We Live Now, and Émile Zola’s L’Argent. Both novels articulate the impact of information on the stock market and trades and they do so by crystallizing a character with the task of disseminating stories about the company they work for. However, these characters distil not only the strategies of advertising and press-directing, but also a certain moral, truth- and history-management. In the artricle we argue first that these characters function rather as placeholders for a specific set of values than as psychological personalities, and second that they lend themselves to a fruitful comparison between French and British literature and economics of the time, in turn fleshing out Trollope’s versus Zola’s view on the potential of a free press and its powers in the financial sphere.